Challenges in setting the environmental agenda in Iran - Maryam Esmaeili Fard; Human Liaghati; Ahmad Saie; Hamidreza Malek Mohammadi (علوم محیطی, 2017)
Introduction: Despite the history of legislative measures in the field of the environment of Iran, the environmental situation of the country based on “the Environmental Performance Index”, “the Global Footprint Network” and “the World Bank” is significantly different from the goal of "Desirable Environment" in the Iran's 20-year vision plan4. In search of the reason, this paper from a public policy perspective seeks to prioritize and explain the challenges of environmental policy making in the Islamic Republic of Iran in the first phase of the Jones staged model.In staged model, the government and decision makers performance are ideally divided into five stages: the process of recognizing the problem and its inclusion on the government agenda(Agenda setting), the stage of the solution proposal (Formulation), the decision-making stage, the stage of implementation and the evaluation stage(Vahid,2004). Materials and methods: The focus of this paper is on the pathology of the recognition and inclusion of the problem in agenda. What is meant by understanding the problem and including of it on the agenda is a process by which ideas and issues are raised through various political institutions to be taken into consideration by a political entity such as the legislative or judicial body. Although there are few places - such as the legislature, the judiciary or the regulatory Commission - that are able to formally formulate policy calendars (agendas), but there are countless sources where subjects of these calendars come from (Shafritz and Borick ,2012).Considering the nature and limitations of the subject literature in our country, from among existing approaches to research , the mixed methods  and exploratory sequential designswere selected. In this formulation of the research project, first the collection and analysis of data is done qualitatively and then quantitatively and ultimately interpreted simultaneously. The main use of this type of research project is to investigate an issue deeply or for the first time for which the researcher does not have a guideline framework or measurement tool for them(Creswell,2003). Results and discussion: Findings of the research showed that the main challenges of environmental policy-making in identifying the problem and placing it in the agenda that led to the decline of quantitative and qualitative indices of the country's vital resources are: prioritizing the country's issues on the basis of economic, political and security considerations (rather than environmental ones), the poor citizen and interest groups participation in identifying and prioritizing local needs, the weak coordination of intergovernmental organizations and government agencies responsible for and influential in environmental issues, the neglect of local communities from the benefits of sustainable development and focus on growth-oriented demands and short-term ones, lack of bottom-to-top mechanisms to express the real  public concerns to be included in the environmental policy calendar, the lack of information and accurate statistics on the status quo and future environmental trends, the lack of attention to communication channels such as the media and the press to transfer issues to higher layers for inclusion in the agenda. Conclusion: Improving Iran's environmental indicators based on the Environmental "Performance Index", "Global Footprint Network" and “World Bank" with the goal of "desirable environment" in the 1404 vision document require solving the challenges of the agenda Setting.